Globalization, Supranational Dynamics and Local Experiences (Europe in a Global Context, 2018)
This edited collection focuses on concepts of globalization, glocalization, transnationalism and cosmopolitanism. The contributions provide evidence of how in practice, global dynamics and individual lives are interrelated. It presents theoretical reflections on how the local, the transnational and global dimensions of social life are entwined and construct the meaning of one another, and offers everyday examples of how individuals and organizations try to answer global challenges in local contexts. The book closely focuses on migration processes, as one of the main phenomena allowing a high number of people from contemporary society to directly experience supranational dynamics, either as migrants or inhabitants of the places where migrants pass through or settle down. Globalization, Supranational Dynamics and Local Experiences will be of interest to students and scholars across a range of disciplines, including sociology, migration studies and global studies.